Bedaquiline, pretomanid, linezolid, and moxifloxacin (BPaLM) for multidrug- or rifampin-resistant tuberculosis: a systematic review - Denise Rossato Silva; Flávia Fonseca Fernandes; Juliana Carvalho Ferreira; Wanderley Bernando; Margareth Maria Pretti Dalcolmo; Fernanda Dockhorn Costa Johansen; Fernanda Carvalho de Queiroz Mello (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To evaluate the available evidence comparing the use of the bedaquiline, pretomanid, linezolid, and moxifloxacin (BPaLM) regimen for 6 months with that of standard-of-care regimens for patients with multidrug-resistant or rifampin-resistant tuberculosis (MDR/RR-TB). Methods: This was a systematic review of clinical trials comparing the use of the BPaLM regimen with the standard of care in patients with MDR/RR-TB. The main outcome measure was an unfavorable endpoint (a composite of death, treatment failure, treatment discontinuation, loss to follow-up, and recurrence), and secondary outcome measures included adverse events and serious adverse events. We searched the MEDLINE, EMBASE, Google Scholar, LILACS, and ClinicalTrials.gov databases, from their inception to January 31, 2024, with no limitation as to language or year of publication. The risk of bias was assessed by using the Cochrane risk-of-bias tool, and the quality of evidence was based on the Grading of Recommendations Assessment, Development and Evaluation approach. Results: A total of 3,668 studies were retrieved; only one (a randomized clinical trial) met the inclusion criteria and was included. In patients with MDR/RR-TB, treatment with the BPaLM regimen, when compared with the standard of care, reduced the risk of an unfavorable outcome (composite, number needed to treat [NNT] = 7); early treatment discontinuation (NNT = 8); adverse events and discontinuation (NNT = 12); and serious adverse events (NNT = 5). Conclusions: This systematic review of the use of BPaLM in patients with MDR/RR-TB, although it included only one study, showed that BPaLM is more effective than is the standard of care and has a better safety profile. That has major implications for guidelines on the treatment of MDR/RR-TB.